Code of Ethics compliance by accountants in Ghana. (2016) - Aveh, Felix Kwame; Awunyo-Vitor, Dadson; Owusu-Afriyie, Richard
The purpose of this study is to identify factors that influence accountants' compliance with the Code of Ethics. Data for the study was collected from a sample of 136 professional accountants in Ghana using a well-structured questionnaire. Descriptive statistics and ordinary least square (OLS) regression model were used to analyse the data with the help of STATA econometric software. The respondents noted that compliance with the Code of Ethics would improve the quality of financial statements. The major causes of non-compliance identified by the respondents are lack or inadequate ethical education, organisational climate and top management support. The OLS regression result revealed that the respondents' awareness and perception of the severity of the penalty positively influence compliance. It is therefore recommended that accountants should be educated adequately on the content of the Code of Ethics and penalties should be enforced when breached. The above can only be achieved if the Institute of Chartered Accountants-Ghana commits more resources to organising CPD programs and seminars on the Code of Ethics and enforces penalties for non-compliance.